Designer is needed with availability to travel... to Mars - Fraile-Narváez, Marcelo (2023)
The exploration and colonization of other planets is a reality that will require designing habitable structures to guarantee the survival and prosperity of the colonists in space. This implies a close collaboration between engineers, scientists and designers. Similarly, it assumes that a new generation of designers has the necessary skills to face these challenges. Therefore, this work aims to investigate the skills, abilities and characteristics required by designers to participate in Mars exploration and colonization projects. For this, three case studies will be analyzed, using the key concepts identified by Raúl Pólit Casillas in his article “Spatial architecture. A new field of practical innovation” (2010). An analysis that represents an opportunity to contribute to the advancement of humanity and explore new frontiers in design.